Stomata Density Analysis of Red Chili (Capsicum annuum L.) at Different Location - N. Nurhaya; Asrullah Syam; Jusmiati Jafar (Universitas Sembilanbelas November Kolaka, 2021)
Red chili (Capsicum annuum L.) is a commodity of vegetable that has high economic value. Stomata are an important part of plant organs, it a gap that role in the process of photosynthesis and plant transpiration. The purpose of this study to determine differences in the stomata density of red chili (Capsicum annuum L.) leaves at different locations, namely locations exposed and shaded from sunlight. This study used a quantitative approach with the type of research used is experiment as by one factor is that sunlight intensity, used two paired treatments and respective of three repetition. The data collection method in this study used direct observation and used analytic method to analyze the stomata density of chili (Capsicum annuum L) leaves. The result of his study showed that the stomata density of red chili (Capsicum annuum L.) leaves differed according to the planting location in the form of locations exposed to sunlight and locations that were shaded. The stomata density planted in a location exposed to full sun had a higher stomata density at 409.9 cells/mm2, while the stomata density of red chili (Capsicum annuum L.) leaves planted in a shaded location had a lower stomata density at 96.9 cells/mm2